Mindfulness dan Kecerdasan Emosional terhadap Kesehatan Mental Siswa Sekolah Menengah Atas - Astuti, Dewi; Partono; Suherman, Heru (LPPM Undiksha, 2025)
Mental health among high school students remains a concern due to the ongoing academic, social, and psychological pressures. Students face various academic and social demands that can trigger stress and disrupt their mental well being. Based on this, the aim of this study is to analyze the influence of mindfulness and emotional intelligence on the mental health of high school students. This study uses a quantitative approach. This study uses an explanatory survey method. The population of this study consisted of 102 high school student respondents. This study chose to use the entire population as its research sample, employing the census technique. Data collection methods used interviews, questionnaires, and observations. The instrument used in this study was a questionnaire sheet. The data analysis technique used includes regression analysis. The results of the study, specifically the F-test results, showed that both emotional intelligence and mindfulness collectively had a significant impact on the mental health conditions of students. The results of the t-test showed that the influence of emotional intelligence on mental health is very strong and statistically significant. The results of the multicollinearity test showed that the two variables did not experience a high correlation that was detrimental to the model, with a Tolerance value of 0.679 and a VIF of 1.473 for both. It was concluded that emotional intelligence has a greater influence on mental health than mindfulness. The implication of the research is that mindfulness and emotional intelligence have an impact on students' mental health, so teachers should consider integrating mindfulness training programs into their curriculum.